Revealing land control dynamics in emerging agricultural frontiers - Olivia del Giorgio; Matthias Baumann; Tobias Kuemmerle; Yann le Polain de Waroux (Proceedings of the National Academy of Sciences, 2025)
The expansion of commodity agriculture into tropical and subtropical woodlands degrades ecosystem functionality, biodiversity, and the livelihood base of millions of people. Understanding where and how agricultural frontiers emerge is thus important. Yet, existing monitoring approaches typically focus on mapping deforestation and do not capture the shifts in land access and ownership that lay the ground for agricultural expansion, thereby missing early stages of frontier development. We develop an approach that captures these early dynamics and apply it to the entire 1,1 million km 2 of the Chaco, a global deforestation hotspot. Through the detection of linear features indicative of land claims and the analysis of their spatial–temporal dynamics, we reveal that the footprint of agricultural frontiers in the region extends far beyond that of deforestation. Most of the Chaco shows signs of land claiming, and although claiming activity is especially concentrated close to active deforestation, emergent claiming in remote parts of the Bolivian and Paraguayan Chaco indicates rapidly growing interest in land in these regions. Finally, the strong spatial correlation between land claiming and the disappearance of smallholder homesteads points to the social repercussions of early agricultural frontier expansion in the Chaco. By offering a transferable template to map land-control indicators at scale, our approach enables a better understanding of frontier processes and more accurate targeting of policy interventions in emerging agricultural frontiers globally.